Social Workers’ Reports on Needs and Recommendations to Enhance School Safety - Natalie Fensterstock; Kate R. Watson; Luz E. Robinson; Vanessa R. Warri; Anthony A. Garcia; Chaoyue Wu; Sawyer Hogenkamp; Yinuo Xu; Hannah Garner; Danielle Dunn; Ron Avi Astor; Dorothy L. Espelage; et al. (Behavioral Sciences)
Issues with school safety and violence have raised concerns that warrant attention from researchers, policy makers, and practitioners alike. In this study, we explored how school social workers—a group of school personnel who are understudied in the school violence literature—experience school safety and violence in the United States. Using a sample of 271 school social workers, we analyzed qualitative responses to two open-ended survey questions: (a) What are the most concerning safety issues facing educators and staff in your school? (b) What policies, procedures, resources, or interventions are needed to better prevent or address violence in your school? Data were collected online between March and June 2022 by the American Psychological Association Task Force on Violence against Educators and School Personnel. Derived using a socioecological framework, findings reflect school social workers’ needs for workplace safety and perspectives on how to prevent and mitigate school violence at the school site, district, and community levels. Implications range from promoting strong relationships in schools and between the school and community to bolstering funding sources that can sustain programs, training, and staffing aimed at improving experiences for all students. The implications of our findings for future research and practice are presented.